"Particle‐on‐plane" hybrid of ZnO‐reduced graphene oxide: Roles on mechanical and tribological performances of thermosetting polyimide. Issue 7 (4th May 2022) - Luo, Rong; He, Yan; Liu, Hong; Wang, Jinqing; Yang, Shengrong
Abstract: In this article, a hybrid of reduced graphene oxide (rGO) sheets decorated by zinc oxide (ZnO) particles was synthesized by a simple hydrothermal method, and its thermosetting polyimide (TPI) composites were prepared by an in situ polymerization method. The mechanical and tribological properties of the ZnO–rGO/TPI composite under dry sliding conditions were studied. The compression strength and modulus of 0.8 wt% ZnO–rGO/TPI composite reached 120.67 ± 2 MPa and 1.77 ± 0.06 GPa, which were 28.1% and 51.3% higher than those of TPI, respectively. The wear rate of 0.8 wt% ZnO–rGO/TPI was also reduced to 1.54 × 10 −8 mm 3 N −1 m −1 at 100 N load, which is about two order of magnitude lower than that of TPI. Compared with the addition of GO alone, the results also demonstrate more significant enhancements in mechanical and tribological properties of TPI by ZnO–rGO hybrid. Furthermore, the tribological mechanism exploration indicates that the "particle‐on‐plane" structure and chemical bonding between ZnO and rGO lead to the crack suppression and strength increment, contributing to the extraordinary improvement of mechanical and tribological properties. Thus, this ZnO–rGO/TPI composite presents promising potential as high‐performance tribological materials under dry‐sliding conditions in industrial applications. Abstract : "Particle‐on‐plane" ZnO‐reduced graphene oxide hybrid (ZnO–rGO) and its thermosetting polyimide composite (ZnO–rGO/TPI) were synthesized, respectively. The ZnO–rGO hybrid showed significant enhancement on mechanical and tribological properties of TPI, which can be mainly attributed to the synergistic effect and chemical bonding between ZnO and rGO.